Analisis Laporan Keuangan UMKM Berdasarkan SAK EMKM Perseroan Perorangan Sekumpul Mart: Kajian Rasio Likuiditas, Solvabilitas dan Profitabilitas - Khansa Kamilah; Mu’nis Nur Hanifah; Putri Fatimatuz Zahra (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The purpose of this study is to determine the financial performance of an MSME company’s financial report using financial ratios, namely liquidity, solvency, and profitability ratios. The tools used in this study are liquidity ratios including Current Ratio (CR) and Quick Ratio (QR), solvency ratios including Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), profitability ratios including Return on Asset (ROA), and Return on Equity (ROE). The research was conducted on the financial report of the MSME Sekumpul Mart for the period 2020-2021. The research method used is a quantitative descriptive method. The results of the study show that there is a positive and significant influence on the financial report, where the position of the financial report is above the general standard of financial ratios (liquidity and solvency). However, the financial report is less significant on the profitability ratio, where the position of the financial report is still below the general standard. The results of this study are expected to provide an overview of the financial condition of MSMEs and become a basis for managerial decision making.